Community Empowerment Through 175 UINSU KKN Work Program in Efforts to Prevent Stutting in Ara Condong Village Stabat District, Langkat District - Putri, Sabila Tamimi; Puspita, Rani; Ramadhani, Khairunisa; Nainggolan, Annisa E.; Sugianto, Sugianto (Jurnal Pengabdian Masyarakat, 2024)
Purpose: The purpose of this seminar is to address the persistent issue of stunting, which remains a serious problem in Indonesia despite a decrease in prevalence from 2.8% to 21.6%. The specific aim is to enhance public health quality by increasing parental knowledge about stunting, particularly in Ara Condong Village, which has a nearly zero stunting rate. Method: The approach involves educational methods and direct observation of parents. The process includes several stages: (1) data collection on stunting issues in the village, (2) obtaining permission from the village office to conduct seminar activities, (3) coordination with posyandu cadres, and (4) socialization of seminar activities to pregnant mothers and mothers with toddlers. Practical Applications: The practical application of this seminar is to provide educational information to parents about stunting, thereby increasing their knowledge and understanding of the issue. This is expected to contribute to the prevention of stunting in Ara Condong Village. Conclusion: Based on the results of the KKN 175 program aimed at preventing stunting in Ara Condong Village, it is hoped that these efforts will improve the quality of human resources in the village. Despite the low stunting rate in the village, the community remains vigilant and proactive in preventing stunting through education and awareness.